Indonesia's Foreign Policy in Digital Era : Poliheuristic Theory - Laode Muhamad Fathun; Laode Muhamad Fathun, Laode Muhamad (Intermestic: Journal of International Studies, 2021)
This paper discusses the consideration of the formulation of Indonesia's foreign policy and diplomacy in the digital era in the economic and social fields. This study uses a qualitative paradigm with a descriptive analysis type. This research uses a case study method with secondary data collection techniques taken from various relevant references such as books, journals and reports and others. So this research uses a research library. The author uses poly-acoustic theory and foreign policy formulations in the digital era. Hasilyang found that the formulation of foreign policy in the digital era contains the question of why it is oriented towards promoting foreign policy, What, is oriented towards policy support in the digital era, who, namely the government, companies and society. Then the question where, in the country and region. And how about through politheuistic. The analysis found that the formulation of Indonesia's foreign policy and diplomacy has two considerations, namely cognitive cognition and rational calculation. Thus, it is concluded that Indonesia's interests in the economic and social fields have a great opportunity to make Indonesia a transforming country in the digital era.